Integrating the History of Mathematics into Foundations of Information Security Mathematics: A Teaching Reform Practice from the Perspective of Curriculum Ideology - Gao, Wei; Li, Mei (International Journal of Social Sciences and Public Administration, 2026)
Foundations of Information Security Mathematics is a core foundational course for information security–related majors, covering topics such as number theory, abstract algebra, and elliptic curves, and other essential mathematical topics. Due to its high level of abstraction, intensive use of formal proofs, and substantial mathematical rigor, students often experience significant learning difficulties and lack sustained motivation. In the context of curriculum ideology and politics in higher education, this paper explores an instructional approach that integrates the history of mathematics and mathematicians’ narratives into classroom teaching. Taking Fermat’s Little Theorem and Euler’s Theorem as representative examples, we analyze how historical narratives can enhance student engagement, deepen conceptual understanding, and foster scientific spirit and academic values. Teaching practice indicates that employing the history of mathematics as an entry point for curriculum ideology facilitates the organic integration of professional knowledge transmission and value education, offering a viable reference for instructional reform in mathematics courses for information security programs.